Schola Be a Volunteer, Succeed at School - Kovačič, Mojca; Pisk, Marjeta; Podjed, Dan (ZRC SAZU, Založba ZRC, 2018)
In this book, we present the results of a two-year project that was carried out by partners in five European countries with the financial support of the EU Erasmus+ programme. The project addressed young people and mentors and helped them understand the importance of non-formal and informal education, supported by volunteering, in preventing early school leaving. In this way, the project team put special attention on recognising the key competences that young people acquire through their voluntary work. The initial goal of the project was to test ideas and concepts at the local levels - to see which approaches are the most appropriate in a certain country, socio-cultural framework and even on a micro-level of schools and other institutions involved in the project. The book offers theoretical contribution on the topic of the project as well as presents the working process from individual countries - Belgium, France, Italy, Poland and Slovenia.